Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1158/0008-5472.can-06-3014
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Expression of Vascular Cell Adhesion Molecule-1 as a New Mechanism for Tumor Immune Evasion

Abstract: Immune escape is an important reason why the immune system cannot control tumor growth, but how escape variants emerge during immunotherapy remains poorly understood. Here, we identify a new mechanism of tumor immune escape using an in vivo selection strategy. We generated a highly immune-resistant cancer cell line (P3) by subjecting a susceptible cancer cell line (P0/TC-1) to multiple rounds of in vivo immune selection. Microarray analysis of P0 and P3 revealed that vascular cell adhesion molecule-1 (VCAM-1) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 52 publications
2
71
0
Order By: Relevance
“…The most widely used methods for this involve examination of differential gene expression in leukemic cells by assessing the mRNA levels in the given cells. Several successful studies reported the feasibility of this approach [22][23][24][25]. On the other hand, this methodology comes from a reductionist point of view, as it neglects the dynamic nature of protein translation and further modifications that take place beyond transcription.…”
Section: Exploitation Of Protein Profiling In Leukemia Researchmentioning
confidence: 99%
“…The most widely used methods for this involve examination of differential gene expression in leukemic cells by assessing the mRNA levels in the given cells. Several successful studies reported the feasibility of this approach [22][23][24][25]. On the other hand, this methodology comes from a reductionist point of view, as it neglects the dynamic nature of protein translation and further modifications that take place beyond transcription.…”
Section: Exploitation Of Protein Profiling In Leukemia Researchmentioning
confidence: 99%
“…A recent report, in which the TC-1 cell line was made resistant to immune eradication in a vaccination based model, identified expression of vascular cell adhesion molecule-1 (VCAM-1) as a potential player in the immune evasion process. 127 Whether VCAM-1 could play a role in tumor eradication in cbl-b -/-mice needs to be determined. In spontaneous skin cancer formation, immune escape has not been observed so far, indicating, that immune escape from cbl-b -/-CD8 + T-cells might only occur in some cancers.…”
Section: Potential Therapeutic Use Of Cbl-b Inhibition In Cancer Immumentioning
confidence: 99%
“…Thus, to determine the role of activated PADRE-specific CD4 + T cells in the proliferation of E7-specific CD8 + T cells, we employed an E7-specific CD8 + T-cell line that expresses luciferase (E7T-LUC). 11 We have previously shown that the luminescence intensity correlates with the number of E7T-LUC cells. 11 We then performed a proliferation assay using E7T-LUC cells incubated with irradiated TC-1 cells into 24-well plates.…”
Section: Resultsmentioning
confidence: 92%
“…11 We have previously shown that the luminescence intensity correlates with the number of E7T-LUC cells. 11 We then performed a proliferation assay using E7T-LUC cells incubated with irradiated TC-1 cells into 24-well plates. PADRE-specific CD4 + T cells (PADRE-CD4) and DCs loaded with or without PADRE were added in wells as indicated in the table of Figure 6a.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation